Pengembangan Kamus Bergambar Bahasa Arab untuk Siswa Kelas I, II, III Madrasah Ibtidaiyah - Saiful Fuad (Prodi PBA Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2020)
In learning Arabic, dictionaries are important thing in helping students understanding vocabulary. Understanding vocabulary does not depend on the translation directly but also requires illustrating the image to make students' understanding is easier.Especially, for students who have learned Arabic inMadrasah Ibtidaiyah. The supporting media in the form of dictionaries are expected to help students to be able to learn independently. The objectives of this study were to: (1) develop Arabic picture dictionary for 1st, 2nd, and 3rdgrade students of Madrasah Ibtidaiyah and, (2) Describe eligibility of developing Arabic picture dictionary for for 1st, 2nd, and 3rd grade students of Madrasah Ibtidaiyah. This study used development theory referring to the R & D model according to Borg and Gall. The subjects in this study were 1st, 2nd, and 3rd grade students of Madrasah Ibtidaiyah Sunan Kalijogo Malang. The types of data in this study are quantitative and qualitative data. The data collection of this study obtained from (1) media expertise, (2) material expertise, (3) Arabic teachers in Madrasah Ibtidaiyah Sunan Kalijogo, and (4) 1st, 2nd, and 3rd grade students of Madrasah Ibtidaiyah Sunan Kalijogo Malang. The results of this study are: (1) Arabic picture dictionary for 1st, 2nd, and 3rdgrade students of Madrasah Ibtidaiyah, consists of 23 chapters that have been grouped according to themes and also classes, and this dictionary is equipped with aphorisms that motivate students in learning (2) eligibility of developing Arabic picture dictionary for 1st, 2nd, and 3rd grade students of Madrasah Ibtidaiyah, declared valid with an average percentage of 86.35% of media experts, material experts, teachers, and students. Based on the results of this study, the researcher got some suggestions, which are: (1) the students,this Arabic picture dictionary can be used inside or outside the classroom to facilitate them to learning Arabic vocabularies. (2) the Arabic teachers, are using this dictionary as a supporting media to improve student learning motivation and as supporting teaching media in the classroom, (3) further researchers and other media developers, this media should be inspected for the imperfections, modified, enhanced, and developed again to make it better supporting media, and (4) Students of the Arabic Language Teaching Study Program, the results of this study can be used as material for another study and as a further development of another Arabic picture dictionary.